2008
DOI: 10.1007/s11130-008-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Micellarisation of Carotenoids from Raw and Cooked Vegetables

Abstract: The efficiency of carotenoid micellarisation from plant foods can be used as an effective tool for the initial screening of carotenoid bioavailability. Therefore, the objectives of the present study were to assess the effects of cooking on the micellarisation of beta-carotene, lycopene, beta-cryptoxanthin and lutein from courgette (zucchini), red pepper and tomato; and, to a minor extent, investigate uptake of lutein by Caco-2 cells from micellar fractions obtained from raw and cooked courgettes. Both raw and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
135
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 41 publications
15
135
5
1
Order By: Relevance
“…In addition, studies indicate a higher relative bioavailability of β-carotene compared with lycopene in the tomato matrix. 6,7,35 The β-carotene content was around 4 mg kg −1 for both studies (Tables 3 and 4), in accordance with previously reported values. 29,34 In tomato, β-carotene is reported to be dissolved in lipid materials in plastoglobulin-type structures, rendering it more susceptible to thermal degradation than lycopene.…”
Section: Follow-up Studysupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, studies indicate a higher relative bioavailability of β-carotene compared with lycopene in the tomato matrix. 6,7,35 The β-carotene content was around 4 mg kg −1 for both studies (Tables 3 and 4), in accordance with previously reported values. 29,34 In tomato, β-carotene is reported to be dissolved in lipid materials in plastoglobulin-type structures, rendering it more susceptible to thermal degradation than lycopene.…”
Section: Follow-up Studysupporting
confidence: 91%
“…25,35 In the current study, lycopene bioaccessibility varied between 1% and 30% (Tables 3 and 5 the amount of lycopene or β-carotene incorporated into micelles. The relative in vitro bioaccessibility of β-carotene was slightly higher than that of lycopene, which is consistent with previous observations.…”
Section: In Vitro Bioaccessibility Of Lycopene and β-Carotenementioning
confidence: 69%
See 1 more Smart Citation
“…The relative hydrophobicity of β-carotene and lycopene, their location and chemical form in the plant matrices, and their transfer between oil droplets and micelles are important, β-carotene in carrots are associated with proteins [36] surrounded by a thick membranous sheet and lycopene is present in the tomato as crystalloids that develop within or along thylakoid bodies [37]. In the study of Ryan et al [38], comparing micellarization and cellular uptake of carotenoids after processing of courgette, red pepper and tomato samples using 4 different cooking procedures, it was also reported that an enhanced release of carotenoids did not necessary lead to a higher micellarization and/or absorption efficiency. Possible reasons for this may be a higher susceptibility of carotenoids for degradation and isomerization when released from the food matrix, and related consequences for the micellarization efficiency and uptake of carotenoids [39].…”
Section: Caco-2 Cell Uptakementioning
confidence: 99%
“…The amount of rapidly digested starch (RDS) was measured in the samples after 20 minutes during the intestinal phase (4) . Polyphenol contents of cooked oat porridges were measured by the Folin-Ciocalteau method (5) both before and after an in vitro digestion procedure (6) and expressed as Gallic Acid Equivalents (GAE). Values are means of three independent experiments.…”
mentioning
confidence: 99%